Toxicology and Pharmacokinetics Study of Intradiscal Injection of Simvastatin in Rabbits - Huang, Xiaodong; He, Wei; Wang, Weiheng; Fan, Quanchun; Ye, Xiaojian; Wu, Zenghui; Lin, Chia-Ying (Frontiers in Pharmacology, 2021)
To test the pharmacokinetics and toxicology of whole organs and tissues after intradiscal injection of simvastatin in rabbits. To provide the information needed to support human clinical trials. Twelve male and twelve female rabbits were randomly divided into four groups: control group (0 mg/ml), low dose group (0.1 mg/ml), medium dose group (1 mg/ml) and high dose group (10 mg/ml). Simvastatin at different concentrations of 10 ul was injected into L3/4, L4/5 and L5/6 intervertebral discs in each group. Poly (ethylene glycol) -poly (lactic-co-glycolic acid) -poly (ethylene glycol) (PEG-PLGA-PEG) polymer as the drug carrier. The pharmacokinetics of blood samples were measured by LC-MS/MS. Cerebrospinal fluid was obtained and the drug concentration was measured. Blood routine, blood biochemistry and urine of all animals were analyzed and evaluated. The heart, kidney, liver and spleen of each animal were observed and weighed. The intervertebral disc tissues were stained with hematoxylin and hematoxylin (H&E), and then qualitatively analyzed by optical microscopy. 28 days after intradiscal injection of simvastatin, 28 days after simvastatin intradiscal injection, there was no significant difference between the weight, food residue, blood routine, blood biochemistry, urine routine results and the weight of each organ in the 4 groups (p>0.05). The serum concentration of simvastatin is lower than the lowest measurable concentration. The histological score of the intervertebral disc in the high-dose group was significantly higher than that in the other three groups at 28 days (p < 0.05). Three doses of simvastatin were injected into male and female animals respectively, showing no toxic effects. Microscopic histological evaluation of the intervertebral disc showed that the high dose group (10 mg/ml) had damage to the intervertebral disc tissue.